Two B-Box Proteins Regulate Photomorphogenesis by Oppositely Modulating HY5 through their Diverse C-Terminal Domains - Job, Nikhil (Plant Physiol, 2018)
The Arabidopsis (Arabidopsis thaliana) BBX family comprises several positive and negative regulators of photomorphogenesis. BBX24, a member of BBX structural group IV, acts as a negative regulator of photomorphogenesis, whereas another member from the same group, BBX21, is a positive regulator. The molecular basis for the functional diversity shown by these related BBX family members is unknown. Using domain-swap lines, we show that the C-terminal regions of BBX24 and BBX21 specify their function. Because both BBX21 and BBX24 work in close association with HY5, we hypothesized that these proteins differentially regulate the levels or activity of HY5 to fulfill their opposite roles. We show that BBX21 can regulate HY5 post-transcriptionally and the two proteins can coordinate to promote photomorphogenesis. By contrast, BBX24 interferes with the binding of HY5 to the promoter of an anthocyanin biosynthetic gene, possibly by heterodimerizing with HY5 and preventing it from binding DNA. Our finding that both BBX21 and BBX24 regulate HY5 activity post-transcriptionally, in opposite ways, suggests that closely related B-box proteins execute contrasting functions through differential regulation of HY5.